METHODOLOGY OF ORGANIZING PROCESS OF INDIVIDUALIZED LEARNING WITH USING ADAPTIVE SYSTEM OF DISTANCE EDUCATION AND KNOWLEDGE CONTROL EDUPRO - Fedoruk, P. I. (Medical Informatics and Engineering, 2012)
The article reveals methodology of organizing process of individualized learning with using adaptive system of distance education and knowledge control EduPro. Methodology give the possibility to form individual structure of learning material, that let us realize great possibilities for adaptation to the beginner’s knowledge level, to students’ skills and abilities, identification of the moment of students’ readiness for transition to more complicated material level, to reflection of interrelations between different functioning indices, to quality of fulfilled tasks and a result of testing.